Levantamento do perfil dos cafeicultores do sul de Minas Gerais - CAMPOS, Wanêssa W. T. (2017)
Coffee is not only a highly appreciated product but also greatly valorized worldwide. The commodity is always in the limelight in academic investigations. Among the items under analysis, the development of its sustainable production process in every aspect is greatly relevant and a sustainable process is currently crucial to attend increasing market demands. Current analysis provides the profile of coffee producers in the rural regions of Machado, Poço Fundo, with other neighboring towns in the south of the state of Minas Gerais, Brazil. Study comprises a comprehensive bibliographic research dealing with different themes involving coffee production. The following themes were developed: coffee production and the different methodologies involved; sustainability proposals applied within the coffee production chain; main diseases that generally attack coffee plantations; pesticides and fertilizers; several points of view on the theme and the use of PPEs when chemical products are applied. Further, field research was undertaken with 225 small coffee producers. Data revealed that rural producers´ schooling level and capacity affect management on the farms. Main results provided a positive co-relationship between the general capacitation of the farmer and good application practices, and between technological investments and employees´ demands. However, concern has been raised with regard to pesticides and fertilizers in coffee plantations. The use of products prepared for other crops and lack of concern on their toxological classification have been identified as significantly dangerous.